Resveratrol attenuates MPP+-induced mitochondrial dysfunction and cell apoptosis via AKT/GSK-3β pathway in SN4741 cells. (10th January 2017) - Zeng, Weijun; Zhang, Wei; Lu, Fangfang; Gao, Li; Gao, Guodong
Highlights: We identify that resveratrol attenuates MPP + -induced mitochondrial dysfunction and cell apoptosis in SN4741 cells. We confirm the underlying mechanism of this protection at least partially through the AKT/GSK-3β pathway. Abstract: Oxidative stress and mitochondrial dysfunction play crucial role in the dopaminergic neurons death, which is the pathological feature of Parkinson's disease (PD). Resveratrol (Res), a polyphenol derived from grapes and blueberries, has been reported to reduce oxidative stress injury and to restore mitochondrial function. In this study, we aimed to explore the underlying molecular mechanism of the beneficial effects of Res against MPP+- induced mitochondrial dysfunction and cell apoptosis in SN4741 cells. The data showed that Res significantly alleviated MPP+- induce cytotoxicity and restored MPP+- induced mitochondrial dysfunction in SN4741 cells. Moreover, Res rescued MPP+- induced a decline on the level of p-AKT, p-GSK-3βand the ratio of Bcl-2/Bax, and an elevation on the expression of Bax and caspase-3, 9. However, inhibition GSK-3β activity clearly abolished the protective effects of Res. Taken together, these results suggest that Res attenuates MPP+- induced mitochondrial dysfunction and cell apoptosis, and these protections may be achieved through AKT/GSK-3β pathway. These also indicate that Res could be a promising therapeutic agent for PD.